Out in the open: behavior's effect on predation risk and thermoregulation by aposematic caterpillars. (20th May 2020) - Nielsen, Matthew E; Mappes, Johanna
Abstract: Warning coloration should be under strong stabilizing selection but often displays considerable intraspecific variation. Opposing selection on color by predators and temperature is one potential explanation for this seeming paradox. Despite the importance of behavior for both predator avoidance and thermoregulation, its role in mediating selection by predators and temperature on warning coloration has received little attention. Wood tiger moth caterpillars, Arctia plantaginis, have aposematic coloration, an orange patch on the black body. The size of the orange patch varies considerably: individuals with larger patches are safer from predators, but having a small patch is beneficial in cool environments. We investigated microhabitat preference by these caterpillars and how it interacted with their coloration. We expected caterpillar behavior to reflect a balance between spending time exposed to maximize basking and spending time concealed to avoid detection by predators. Instead, we found that caterpillars preferred exposed locations regardless of their coloration. Whether caterpillars were exposed or concealed had a strong effect on both temperature and predation risk, but caterpillars in exposed locations were both much warmer and less likely to be attacked by a bird predator (great tits, Parus major ). This shared optimum may explain why we observed so little variation in caterpillar behavior and demonstrates the important effects of behavior on multiple functions of coloration. Abstract : Predation and temperature are two major forces that influence survival. We found that wood tiger moth caterpillars frequently bask in exposed locations, although this should also expose them to predators. Nevertheless, in our experiments, exposed caterpillars both stayed warmer and were attacked less by birds compared with hidden caterpillars. Warning coloration, thus, protects these caterpillars from birds, but more so if these caterpillars are easily found.